Communication policy in the plans of the Workers' Party (PT) between 1989 and 2014 - Da Silva Lopes, Ivonete (2019)
This paper discusses how the theme policy of communication had treated by the Workers' Party (PT) over the years in its government plans. The analysis comprises 25 years, between 1989 and 2014. During this period were held seven elections for the Brazilian president, and four terms were elected Luiz Inácio Lula da Silva (2003-2010) and Dilma Rousseff (2011-2016). It is adopted as a methodology a documental research and content analysis of the proposals submitted by the PT candidates. The study reveals inconsistencies between party orientations in this field and government practices, as well as evidence that the PT's commitment to regulate communication was fading with each disputed election. The party itself has recently recognized that one of the misconceptions committed during the four terms of office was not to have democratization of the media as one of the priority tasks.